Aplicações de equações diferenciais ordinárias - Ribeiro, Mateus Torres (Universidade Federal do Tocantins, 2025)
This work deals with a study on ordinary differential equations through the presentation of some of the main analytical methods for solving ordinary differential equations alongside the exhibition of applications of these equations in everyday problems. With the research question “What applications and chemical, physical, biological, social sciences, or economic phenomena motivated the study of certain ordinary differential equations whose analytical methods of resolution are studied in the curricular component of Ordinary Differential Equations in higher education?” we arrived, through an exploratory research, at some answers such as: determining the time of death of a person, determining the half-life of radioactive substances, problems involving falling bodies, and population dynamics. In the paper, we present in detail some of these applications found in the literature and also adapted by the author.